Efektivitas Inovasi Intervensi Keperawatan Mengulum Es Batu Terhadap Skala Haus Pasien Hemodialisis - Liza Fitri Lina; Haifa Wahyu (Fakultas Ilmu Kesehatan, Universitas Muhammadiyah Bengkulu, 2019)
Patients with chronic renal failure undergoing hemodialysis often feel thirsty due to the presence of a recommended fluid restriction program. Sucking ice cubes is one of the many methods of managing thirst in CKD patients. The purpose of this study was to determine the Effectiveness of Nursing Innovation in Ice Cubes Nursing Interventions to reduce the thirst scale of chronic renal failure patients undergoing hemodialysis at RSUD dr. M. Yunus Bengkulu. This type of research will be used is quantitative research with a pre-experimental approach using one group design pre-test and post-test. The results of the univariate analysis found that most respondents were female with a total of 8 people (60.0%), most of the respondents' thirsty scale before sipping ice jeger was a heavy thirst that was as many as 7 people (46.7%). After being given the intervention of drinking ice jeger, most of the thirst scale decreased to moderate thirst as many as 11 people (73.4%) and 1 person weight (6.7). Bivariate analysis results obtained Ï Value 0.001 (<0.05). In conclusion, there is an influence of cold suction on the reduction of thirst in chronic kidney failure patients undergoing hemodialysis at RSUD Dr. M. Yunus Bengkulu. This research can be a management / therapy that can be applied to reduce thirst complaints both at home and in the hospital.Â Key words: chronic kidney failure, hemodialysis, sucking ice cubes, thirst scale